Implications of Failure to Routinely Diagnose Resistance to Second-Line Drugs in Patients With Rifampicin-Resistant Tuberculosis on Xpert MTB/RIF: A Multisite Observational Study. (12th February 2017) - Jacobson, Karen R.; Barnard, Marinus; Kleinman, Mary B.; Streicher, Elizabeth M.; Ragan, Elizabeth J.; White, Laura F.; Shapira, Ofer; Dolby, Tania; Simpson, John; Scott, Lesley; Stevens, Wendy; van Helden, Paul D.; et al.
Summary: We report the proportion of rifampicin-resistant tuberculosis patients with drug-susceptibility test (DST) results, the time delay until DSTs were available, and high proportion of baseline second-line DST resistance in South Africa with implications for therapeutic design and treatment outcomes. Abstract: Background: Xpert MTB/RIF (Xpert) detects rifampicin-resistant tuberculosis (RR-tuberculosis), enabling physicians to rapidly initiate a World Health Organization–recommended 5-drug regimen while awaiting second-line drug-susceptibility test (DST) results. We quantified the second-line DST results time and proportion of patients potentially placed on suboptimal therapy. Methods: We included RR-tuberculosis patients detected using Xpert at the South African National Health Laboratory Services (NHLS) of the Western Cape between November 2011 and June 2013 and at Eastern Cape, Free State, and Gauteng NHLS between November 2012 and December 2013. We calculated time from specimen collection to phenotypic second-line DST results. We identified isoniazid and ethionamide resistance mutations on line probe assay and performed pyrazinamide sequencing. Results: Among 1332 RR-tuberculosis patients, only 44.7% (596) had second-line DST for both fluoroquinolones and second-line injectable: 55.8% (466 of 835) in the Western Cape and 26.2% (130 of 497) in the other provinces. Patients with smear negative disease and age ≤10 years were less likely to have a result (risk ratio [RR] = 0.72; 95% CI, 0.64–0.81 and RR = 0.49; 95% CI, 0.26–0.79). Median time to second-line DST was 53 days (range, 8–259). Of the 252 patients with complete second-line DST, 101 (40.1%) potentially initiated a suboptimal regimen: 46.8% in the Western Cape and 25.3% in the other provinces. Conclusions: Many South Africans diagnosed with RR-tuberculosis by Xpert initiate a suboptimal regimen, with information to adjust therapy available in half of all patients after a median 7 weeks. Algorithm completion and time delays remain challenging.